Thinking Critically about Research: A Step by Step Approach, 1st edition - Ogden, Jane (Routledge, 2020)
We live in an age of unprecedented access to information. The last decade has seen an exponential growth in data and material available, often at the touch of a button. However, this has also made it harder to discern between fact and fiction. What is real and what is fake? What should we believe and what should we reject?